ISLAM MODERATE IN INDONESIA - Ahmad Faqihuddin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
Islam is a religion of peace, meaning that Islam does not justify violent practices, in a radical way to achieve a political goal or to maintain a belief that is considered sacred. Religion, which should be a guide for a friendly and tolerant life, has resulted in violence and terrorism. This means that there is a mistake in understanding and implementing fundamental religious teachings. Isn't it the opposite, Islam taught by the Prophet Muhammad SAW, in fact, proves to be a religion that upholds peace, compassion, and respects peace? The mission of Islam brought by the Prophet Muhammad SAW to mankind is peace (salam), this is why this religion is not called Mohammadanism, Arabism, or other isms, but this religion is called Islam which means safety, peace and peace, anyone who preaches Islam must have the principle of prioritizing peace not the other way around. Terrorism and religious radicalism are actually not only a problem of the perpetrators, and not the people who are victims of these actions, but terrorism and radicalism that must be paid attention to are problems of theological beliefs, meaning that the perpetrators can be arrested, imprisoned, and killed, but ideological beliefs and doctrines are not easily abolished. Therefore, it is necessary to discuss a friendly, tolerant, and soothing paradigm of Islamic understanding. This understanding is more suitable for Islamic moderation (Islam Wasathiyah). Islam adalah agama damai, artinya Islam tidak membenarkan praktek kekerasan, dengan cara radikal untuk mencapai suatu tujuan politik atau untuk mempertahankan keyakinan yang dianggap suci, sangat tidak Islami. Agama yang seharusnya menjadi panduan hidup yang ramah dan toleran jusru menjadi timbulnya kekerasan dan terorisme. Hal ini berarti ada kesalahan dalam memahami dan mengimplementasi ajaran agama yang fundamental. Bukankah sebaliknya, Islam yang diajarkan oleh Nabi Muhammad SAW, justru membuktikan sebagai agama yang menjunjung tinggi perdamaian, kasih sayang, dan memahargai perdamaian? misi Islam yang dibawa oleh Nabi Muhammad SAW kepada ummat manusia adalah perdamaian (salam), dari sinilah mengapa agama ini tidak dinamakan Mohammadanisme, Arabisme, atau isme lain, akan tetapi agama ini dinamakan Islam yang berarti selamat, tentram dan damai, siapapun yang mendakwahkan Islam harus berprinsip mengutamakan perdamaian bukan sebaliknya. Terorisme dan radikalisme agama sebenarnya tidak hanya masalah pelakunya, dan bukan pula para orang-orang yang menjadi korban dari aksi tersebut, akan tetapi terorisme dan radikalisme yang harus di perhatikan adalah masalah keyakinan teologis, artinya pelaku bisa ditangkap, dipenjarakan, dan dibunuh, akan tetapi keyakinan dan doktrin ideologinya tidak mudah dihapuskan begitu saja. Oleh karena itu, perlu mewacanakan paradigma pemahaman keislaman yang ramah, toleran, dan menyejukkan. Pemahaman ini lebih cocok pada moderasi Islam (Islam Wasathiyah)